“The whole sky has broken down on me. I might die alone”: A qualitative study on the lived experiences of COVID-19 positive frontline workers in Bangladesh - Arefin, Shamsul; Rashid, Tamanna; Bhattacharjee, Mowsume; Habib, Md. Didarul; Islam, Md. Ashraful; Rahaman, Mohammad Anisur (Frontiers in Sociology, 2022)
Many countries, including Bangladesh, have conducted research on the mental health of frontline workers and their challenges in adjusting to their new workplaces. However, the authors are unaware of any studies on their real-life experiences as COVID-19-positive patients in Bangladesh. This study intends to investigate the lived experiences of Bangladeshi frontline workers who were isolated as a result of the COVID-19 infection and tested positive for the virus. We used a qualitative methodology and a semi-structured interview guide to conduct ten interviews between July 26 and August 12, 2020. The participants were recruited via a social media campaign and purposive sampling. All interviews were conducted via telephone and online and were transcribed and analyzed using Colaizzi's phenomenological method. The study does, however, identify four primary themes and 13 supporting themes, including (1) experience in a new working environment (subthemes: workload and adaptation, maintaining health protocol and social distance, and the fear of infection), (2) diagnosis (subthemes: the origin of infection, physiological problems, experiences at the diagnosis center), (3) recovery days (subthemes: earlier reactions, experiences in isolation, coping mechanisms), and (4) post-COVID-19 (subthemes: excitement, fear, and confusion; physiological problems; increased religiosity; and changes in philosophy). This study is important for healthcare policymakers because it helps them design healthcare management systems that take Bangladeshi society's social context into account. This study also recommends that long-term behavioral change programs be implemented by national policymakers to lessen societal stigma. At the same time, it suggests that the government should help lessen the barriers to health care services that persons with lower socioeconomic status confront.